2015
DOI: 10.3390/ijerph120302905
|View full text |Cite
|
Sign up to set email alerts
|

Centile Curves and Reference Values for Height, Body Mass, Body Mass Index and Waist Circumference of Peruvian Children and Adolescents

Abstract: This study aimed to provide height, body mass, BMI and waist circumference (WC) growth centile charts for school-children, aged 4–17 years, from central Peru, and to compare Peruvian data with North-American and Argentinean references. The sample consisted of 8753 children and adolescents (4130 boys and 4623 girls) aged 4 to 17 years, from four Peruvian cities: Barranco, La Merced, San Ramón and Junín. Height, body mass and WC were measured according to standardized techniques. Centile curves for height, body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 30 publications
4
33
0
10
Order By: Relevance
“…Thus, gender and adiposity should be accounted for in studies examining metabolic and cardiovascular outcomes. Similar to previous studies [35][36][37], age has also been positively associated with abdominal adiposity and fat-free mass. Despite the difference observed between the mean age of the children included in the cohort study and the children who did not conclude the study, this result probably did not affect the associations observed between age and the outcomes investigated.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, gender and adiposity should be accounted for in studies examining metabolic and cardiovascular outcomes. Similar to previous studies [35][36][37], age has also been positively associated with abdominal adiposity and fat-free mass. Despite the difference observed between the mean age of the children included in the cohort study and the children who did not conclude the study, this result probably did not affect the associations observed between age and the outcomes investigated.…”
Section: Discussionsupporting
confidence: 81%
“…15 We opted for these references because they were the latest available ones and exhibited regional characteristics with similar human development indexes (HDI) in recent years.…”
Section: Methodsmentioning
confidence: 99%
“…Bustamante et al 17 compared WC reference values of Peruvian children with other international references. The WC Peruvian children values (4-17 yrs) were lower than the ones for North-Americans and Argentinean children of all ages.They have found that WC differences between Peruvian and NorthAmerican children were of ~5.4 cm in boys and ~6.6 cm in girls, while for Peruvian and Argentinean children were it was of ~2.8 cm in boys and ~3.9 cm in girls aged between 6 and 13.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, developed [12][13][14] and developing [15][16][17][18] countries have established WC percentile reference curves for their children. Portuguese and Brazilian 6-10-year-old children do not have a percentile curves with normative parameters according to the national and international comparisons.…”
Section: Introductionmentioning
confidence: 99%